Preparing for the last fling - Odelia Muller (AOSIS, 1981)
Re t i r e m e n t - the last flin g - seems to be a phenomenon peculiar to the present age and culture which is geared to suit the convenience of the social system rather than the needs of the individual. In the Western world alone 291 million people are over the age of 60 and every day 14 thousand individuals, irrespective of their potential contribution to industry, commerce and state, are scheduled to retire.